A cross-sectional study on the understanding and attitudes toward influenza and influenza vaccines among different occupational groups in China - Xinkun Zhao; Xin Hu; Junyi Wang; Mingshuai Shen; Kaifeng Zhou; Xianjie Han; Milton Thomas; Kezhou Wang; Li Wang; Zhao Wang (Human Vaccines & Immunotherapeutics)
This study aimed to assess the level of knowledge regarding influenza viruses and vaccines among different professional groups to investigate the reasons for vaccine hesitancy. We collected 2190 questionnaires regarding influenza vaccines in China in 2022. The respondents were categorized into the general population (GP), foreign affairs workforce population (FAWP), and veterinary workforce population (VWP) according to their job positions. Linear regression was used to assess the association between multiple factors and influenza vaccination rates. The association between work and influenza vaccination rates was also assessed by grouping different workforce populations. The vaccination rate of the GP was higher than that of the VWP (odds ratio: 1.342, 95% confidence interval: 1.025–1.853), surpassing the rates reported in previous studies. This may be attributed to heightened concerns about infectious diseases influenced by the ongoing coronavirus disease 2019 pandemic. Despite the VWP’s more in-depth knowledge of the VWP on zoonotic diseases and their recognition of their importance, there was no significant difference in influenza knowledge among the three populations. This discrepancy contrasts with the observed differences in vaccination rates. Further investigation revealed that, compared with FAWP, the price of vaccines emerged as a primary influencing factor for vaccination rates (odds ratio:0.398, 95%CI; 0.280–0.564). General concerns regarding the protective effects and side effects of vaccines were also noted.